, 24.01.2020Kkampudiaa

If f(x) = -4x2 - 6x- 1 and g(x) = -x2 - 5x + 3, find (f+ g)(x). o a. (f+ g)(x) = 5x2 + 11x+ 4 o b. (f+ g)(x) = - 5x2 - 11x + 2 o c. (f+g)(x) = -5x2 - x-4 o d. (f+9)(x) = 3x2 + x+4

f(x)  -  g(x)
=>  (3x²  +  x  - 3)  -  (x² - 5x + 1)
=>  3x² + x - 3 - x² + 5x - 1
=>  3x² - x² + x + 5x - 3 - 1
=>  2x² + 6x - 4
Substitute the two functions according to a given condition of function:
f(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
= 3x² + x - 3 - x² + 5x - 1
= 2x² + 6x - 4  or  2(x² + 3x - 2)
I hope this helps you
F(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
f(x) - g(x) = 3x² + x - 3 - x² + 5x - 1
f(x) - g(x) = 3x² - x² + x + 5x - 3 - 1
f(x) - g(x) = 2x² + 6x - 4
Easy peasy, since equals, just sub

f(x)-g(x)
(3x^2+x-3)-(x^2-5x+1)
distribute invisible -1
3x^2+x-3-x^2+5x-1
rearange terms or group like terms
3x^2-x^2+x+5x-3-1
2x^2+6x-4

f(x)-g(x)=2x^2+6x-4

Step-by-step explanation:

3+x-3= - 5x

combine like terms

3 += 4

x -5x = -4x

then combine 4 and -4x

O C. (f – g)(x) = -3x^2 - x - 4

Step-by-step explanation:

I will assume that f(x) is -4x^2- 6x - 1

f(x) = -4x^2 - 6x - 1

g(x) = -x2 - 5x + 3

(f - g)(x)= -4x^2 - 6x - 1  - (-x2 - 5x + 3)

Distribute the minus sign

(f - g)(x)= -4x^2 - 6x - 1  +x2 + 5x - 3

Combine like terms

(f - g)(x)= -3x^2 - 1x - 4

3x^2 + x - 3 - (x^2 - 5x + 1) =
3x^2 + x - 3 - x^2 + 5x - 1 =
2x^2 + 6x - 4 <===

B

Step-by-step explanation:

-4x2 + (-x2)= (-6x2) (-6x) + ( -5x)= (-11x) (-1) + 3= 2-6x2-11x+2

Step-by-step explanation:

f(x) = -4x^2 - 6x - 1   g(x) = -x^2 - 5x + 3

find (f + g)(x)

-4x^2 - 6x - 1 + (-x^2 - 5x + 3) =

-4x^2 - 6x - 1 - x^2 - 5x + 3 =

-5x^2 - 11x + 2 <

Other questions on the subject: Mathematics

Mathematics, 21.06.2019, ashiteru123
answer: the answer is simply nothing.step-by-step explanation: because there is no ending to this question gimme brainliest > : 3...Read More
Mathematics, 21.06.2019, 341404143
sorry, i'm new here and i'm just trying to figure this out. try quizlet. rate 5* you!...Read More